Effects of different ozone treatments on the storage quality and stability of fresh peeled garlic. Issue 37 (28th June 2021) - Liu, Hong; Xu, Lin; Yu, Fengling; Tan, Jia; Cao, Lin; Xing, Yage; Xu, Qinglian; Yang, Shuang; Liu, Xiaocui; Yang, Ping; Yue, Tianyi; Wang, Xiaomin; et al.
Abstract : In order to understand their impacts on the preservation of fresh garlic, varying concentrations of ozone gas and different storage temperatures were tested for this experiment. Abstract : In order to understand their impacts on the preservation of fresh garlic, varying concentrations of ozone gas and different storage temperatures were tested for this experiment. The results demonstrated that freshly peeled garlic was best preserved by an ozone concentration of 5 ppm and storage at 4 °C compared to other treatment groups. With these optimized conditions, after 25 days of storage, the weight of garlic decreased by only 1.89% and, under the same storage conditions, the water loss rate was only 65.17% that of the control group, with a decay rate of only 12.50%. The rate of decay in the blank control group was three times that of this group. The germination rate was also low: only 30.26%, which was 57.69% that of the blank control group. The hardness was measured at 7.48 kg cm −2, 19.79% higher than that of the blank group. The content of soluble solids was 9.15 g 100 mL −1, which was 10.27% higher than that of the blank group, again proving that the above storage parameters were effective. At the same time, the titratable acid (TA) in the garlic was 15.48%, which was 1.17 times that of the blank group and corresponds to the vitamin C content. Also, the content of diallyl trisulfide only decreased by 3.98% and was 11.2% higher ( P < 0.01) than that of the blank group. Finally, the validity of this optimal result was also confirmed by sensory evaluation. These results, for garlic, support the application of ozone as a safe, non-thermal preservation technique benefiting both producers and consumers.